Phytochemicals: Promising Inhibitors of Human Rhinovirus Type 14 3C Protease as a Strategy to Fight the Common Cold - Tsilimingkra, Nefeli Theodora; Papaneophytou, Christos (Current Topics in Medicinal Chemistry, 2024)
Background: Human rhinovirus 3C protease (HRV-3Cpro) plays a crucial role in viral proliferation, establishing it as a prime target for antiviral therapy. However, research on identifying HRV-3Cpro inhibitors is still limited. Objective: This study had two primary objectives: first, to validate the efficacy of an end-point colorimetric assay, previously developed by our team, for identifying potential inhibitors of HRV-3Cpro; and second, to discover phytochemicals in medicinal plants that inhibit the enzyme's activity. Methods: Rupintrivir, a well-known inhibitor of HRV-3Cpro, was used to validate the colorimetric assay. Following this, we conducted a two-step in silico screening of 2532 phytochemicals, which led to the identification of eight active compounds: apigenin, carnosol, chlorogenic acid, kaempferol, luteolin, quercetin, rosmarinic acid, and rutin. We subsequently evaluated these candidates in vitro. To further investigate the inhibitory potential of the most promising candidates, namely, carnosol and rosmarinic acid, molecular docking studies were performed to analyze their binding interactions with HRV-3Cpro. Results: The colorimetric assay we previously developed is effective in identifying compounds that selectively inhibit HRV-3Cpro. Carnosol and rosmarinic acid emerged as potent inhibitors, inhibiting HRV-3Cpro activity in vitro by over 55%. Our analysis indicated that carnosol and rosmarinic acid exert their inhibitory effects through a competitive mechanism. Molecular docking confirmed their competitive binding to the enzyme's active site. Conclusion: Carnosol and rosmarinic acid warrant additional investigation for their potential in the development of common cold treatment. By highlighting these compounds as effective HRV-3Cpro inhibitors, our study presents a promising approach for discovering phytochemical inhibitors against proteases from similar pathogens.
Keywords: Molecular docking